Zakat as an Effective Strategy for Poverty Alleviation in Zanzibar - Abdalla Ussi Hamad (Center of Strategic Studies (PUSKAS) BAZNAS, 2023)
It is well known that the basic objective of paying Zakat is to create a balance in the society and never let a poor and needy suffer or die. In simplicity, the wealth is transferred from the hands of rich to poor in order to stabilize economic condition of the society and ensures that each person is benefitted from the wealth. The main purpose of this paper is see how zakat is used as an Islamic instrument for poverty alleviation in Zanzibar. A quantitative approach was used in this study where a sample size of 287 head of households was used. A survey questionnaire was used as data collection instrument. To achieve a credible study, Structural Equation Modeling (SEM), based on maximum likelihood estimation, and relevant analyses were used to analyse the collected data from relevant respondents. The results indicate that people have access to and uses of zakat fund but there is no any impact on their quality of life due to several challenges such as low amount of distribution and poor management of zakat fund. The study has offered several recommendations with regard to the means and practices of poverty alleviation in Zanzibar via Zakat fund.